Analysis of the Implementation of Global Reporting Initiative (GRI) 200 Indicators in Sustainability Reports of Energy Sector Companies on the Indonesia Stock Exchange in 2023 - Haryono Haryono; Eicha Febrianti Hasnah; Nur Nabila (Asosiasi Dosen Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of the Global Reporting Initiative (GRI) 200 indicators in the sustainability reports of energy sector companies listed on the Indonesia Stock Exchange in 2023. Using a qualitative approach through content analysis of 70 companies, the study found that disclosure of economic aspects remains inconsistent and tends to be narrative rather than quantitative. Of all the indicators, GRI 201-1 on economic value generated and distributed is the strongest indicator due to its relatively clear disclosure by companies, while GRI 206-1 on legal action for anti-competitive behavior is the weakest indicator due to minimal disclosure. These findings highlight the gap between sustainability transparency demands and current economic reporting practices. Therefore, improving the consistency, depth, and quantification of information is necessary for sustainability reports to truly serve as comprehensive and credible accountability instruments. This also opens up opportunities for further research to strengthen the disclosure of indicators that remain weak